PEMETAAN PROFIL DAN KOMPETENSI GURU PENDIDIKANJASMANI DAN KESEHATAN TINGKAT SEKOLAH DASARDI KOTA BENGKULU - Dian Pujianto dan Bayu Insanistyo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractThe competence of a teacher is very important in education, especially in primary education. Since the right field ofcompetence is in accordance with the teacher’s quality, it will provide and produce the finest quality of the students.The data collection techniques were using a survey method. The results of this study illustrate the pedagogicalcompetence of the teacher is at 50.1% of teachers who are already qualified, while 40.9% of teachers have notachievethe pedagogical competence yet, personal competence shows that 95.5% of the teachers are competentand 4.5% of teachers have not been competent yet. Professional competence of the teachers shows that 46.6%are competent, and 53.4% of the teachers have not achieve the professional competence yet, social competenceshows that 65.92% of the teachers are competent, but there are 34.02% of the teachers who have not been able tomaster social competence. From these results, it can be concluded that Physical Education teachersfor elementaryschools in the town of Bengkulu have not mastered the entire competence as the educator.Keywords: Competence, Physical Education Teacher.AbstrakKompetensi seorang guru sangat penting dalam pendidikan, terutama pada pendidikan dasar. Karena dengankompetensi yang sesuai dengan bidangnya seorang guru akan memberikan dan menghasilkan anak didik yangberkualitas. Teknik pengumpulan data yang digunakan dalam penelitian ini menggunakan metode survei. Hasilpenelitian ini menggambarkan kompetensi pedagogi ada 50,1% guru yang sudah berkompeten sedangkan 40,9%guru belum memiliki kompetensi pedagogi , kompetensi kepribadian telah menunjukkan 95,5% guru berkompetendan 4,5% guru belum berkompeten. Kompetensi profesional menunjukkan 46,6% guru berkompeten, dan 53,4% gurubelum memiliki kompetensi profesional, kompetensi sosial menunjukkan bahwa 65,92% guru telah berkompeten, akantetapi masih ada 34,02% guru yang belum mampu menguasai kompetensi sosial. Dari hasil ini dapat disimpulkanbahwa guru pendididkan jasmani sekolah dasar di kota Bengkulu belum menguasai seluruh kompetensi sebagaiseorang pendidik.Kata Kunci: Kompetensi, Guru Penjaskes.